STRUCTURAL EVOLUTION OF THE TELETSK GRABEN (RUSSIAN ALTAI) - Dehandschutter B.; Vysotsky E.; Delvaux D.; Klerkx J.; Buslov M.M.; Seleznev V.S.; Batist M.De. (My University, 2002)
Lake Teletskoye in the northeastern part of the Altai mountain range has attracted the attention of geo-scientists for a long time, because it fills an impressive tectonic depression. The lake is 77 km long and 4 km wide, and it has a maximum water depth of 325 m. The vertical offset of the basement surface is up to 3000 m. A multidisciplinary study of the Teletsk graben was carried out during the last few years, including satellite image and air photo analysis, bathymetric-, structural- and geomorphological mapping, high-resolution seismic profiling and seismic refraction. The structural study revealed that reactivation of preexisting weak basement zones is important in controlling the basin formation. These zones separate different tectonic terranes at the contact of which the Teletsk graben developed.
Keywords: Neotectonics; Seismics; Structural basin evolution; Altai; Lake Teletskoye